Transisi Media Tradisional Ke Digital (Studi Kasus Pada Media Lokal Di Bengkulu) - Sri Dwi Fajarini; Juliana Kurniawati; Fitria Yuliani (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study discusses the transition of traditional to digital media in local media in Bengkulu, which faces significant challenges such as limited human resources, technological infrastructure, and changes in audience consumption behavior. The purpose of this study is to analyze the adaptation strategies of local media in the face of digitalization and its impact on business models and audience engagement. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, participatory observations, and documentation from four main local media: BE TV, RB Koran, Tribunnews Bengkulu, and Radio Jazirah. The data analysis technique used is thematic analysis according to Braun and Clarke. The results show that the media transition takes place in five stages: introduction, adaptation, development, integration and innovation, and evaluation and adjustment. Local media are starting to integrate various digital platforms to increase reach and interaction with audiences. However, challenges related to mastering technology and financing are still the main obstacles. This research confirms that the success of local media transformation depends on content innovation, strengthening human resource capacity, and the ability to manage sustainable digital business models.